2012
DOI: 10.2118/139622-pa
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Fluid-Loss Properties and Return Permeability of Energized Fracturing Fluids

Abstract: Summary With the growing interest in low-permeability gas plays, foam* fracturing fluids are now well established as a viable alternative to traditional fracturing fluids. Present practices in energized fracturing treatments remain, nonetheless, rudimentary in comparison to other fracturing-fluid technologies because of our limited understanding of multiphase fluid-loss and phase behavior occurring in these complex fluids. This paper assesses the fluid-loss benefits introduced by energizing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…The shear modulus is calculated using μ=Vs2ρm(0.3em17.43.0235ptGPa). The viscosity of the slurry is around 0.025–0.15 Pa s [ Ribeiro and Sharma , ], which is significantly larger than the viscosity of water (0.001 Pa s).…”
Section: Discussion and Implications For Hydraulic Fracturing Mechanismsmentioning
confidence: 99%
“…The shear modulus is calculated using μ=Vs2ρm(0.3em17.43.0235ptGPa). The viscosity of the slurry is around 0.025–0.15 Pa s [ Ribeiro and Sharma , ], which is significantly larger than the viscosity of water (0.001 Pa s).…”
Section: Discussion and Implications For Hydraulic Fracturing Mechanismsmentioning
confidence: 99%
“…Compared with conventional fracturing fluids, no filter cake exists in the fracture when the SC‐CO 2 penetrates the unconventional natural gas reservoir. The reservoir formation can be divided into the invasion region and the undisturbed gas reservoir region . For conventional hydraulic fracturing, it is normally assumed that the fracturing fluid is incompressible, and parameters, such as its density and viscosity, are constant; therefore, the Joule–Thomson coefficient term is usually ignored, as shown in Figure .…”
Section: Two‐phase Filtration Rate Modelmentioning
confidence: 99%
“…Lab experiment on fluid lose remains to be the most efficient tool to study the multi-phase fluid leak off(K.E. Friehauf, 2009;Harris, 1983Harris, , 1987Ribeiro & Sharma, 2012). Researches have indicated that foam fracturing fluid has excellent performance on reducing fluid leak off; filter cake can form on fracture surface when wall-building materials such as hydroxypropyl guar (HPG) is added; bubbles can accumulate on the surface of fracture or filter cake; foam can leak off into and penetrate high permeable (~100mD) core, while the two phases can penetrate lower permeable (~10mD) core with different quality from inlet foam; the leak off coefficient depends on foam quality, continuous phase viscosity(wall-building material content), permeability and pressure difference.…”
Section: Multi-phase Fluid Leak Offmentioning
confidence: 99%
“…Therefore, N 2 -energized fluid, CO 2 -energized fluid, N 2 -foam and CO 2 -foam have been widely applied especially in water-sensitive formation. These multi-phase energized fracturing fluids are able to help control fluid leak off and assist load fluid recovery during flow back, and are called foam if the volume percentage of gas to the total fluid is higher than 52% (Ribeiro & Sharma, 2012). This study focuses on the static fluid leak off after fracturing, flow back efficiency of different fracturing fluids and the influence of formation damage on well after-stimulation productivity.…”
Section: Introductionmentioning
confidence: 99%